A new species of Luisia (Orchidaceae: Epidendroideae: Vandeae) from the Western Ghats of India - Karuppusamy, Subbiah; Ravichandran, Vellingiri (Phytotaxa, 2019)
A new species of Luisia megamalayana (Orchidaceae) is described and illustrated from Megamalai Wildlife Sanctuary of southern Western Ghats of India.